Freshening increases the susceptibility to heat stress in intertidal mussels (Mytilus edulis) from the Arctic. - Nielsen, Martin B; Vogensen, Trine K; Thyrring, Jakob; Sørensen, Jesper G; Sejr, Mikael K (Wiley, 2021)
Funder: William Demant Fonden Funder: DANCEA Funder: Familien Hede Nielsens Fond; Id: http://dx.doi.org/10.13039/501100007438 Funder: Selskabet for Arktisk Forskning og Teknologi Funder: Aage V. Jensens Fond; Id: http://dx.doi.org/10.13039/501100002721 Temperatures in the Arctic are increasing at a faster pace than at lower latitudes resulting in range expansion of boreal species. In Greenland, the warming also drives accelerating melt of the Greenland Ice Sheet resulting in more meltwater entering Greenland fjords in summer. Our aim was to determine if increasing summer temperatures combined with lower salinity can induce the expression of stress-related proteins, for example, heat shock protein, in boreal intertidal mussels in Greenland, and whether low salinity reduces the upper thermal limit at which mortality occurs. We conducted a mortality experiment, using 12 different combinations of salinity and air temperature treatments during a simulated tidal regime, and quantified the change in mRNA levels of five stress-related genes (hsp24, hsp70, hsp90, sod and p38) in surviving mussels to discern the level of sublethal stress. Heat-induced mortality occurred in mussels exposed to an air temperature of 30°C and mortality was higher in treatments with lowered salinity (5 and 15‰), which confirms that low habitat salinity decreases the upper thermal limit of Mytilus edulis. The gene expression analysis supported the mortality results, with the highest gene expression found at combinations of high temperature and low salinity. Combined with seasonal measurements of intertidal temperatures in Greenland, we suggest heat stress occurs in low salinity intertidal area, and that further lowered salinity in coastal water due to increased run-off can make intertidal bivalves more susceptible to summer heat stress. This study thus provides an example of how different impacts of climate warming can work synergistically to stress marine organisms.